Comparativo de custos entre alvenaria estrutural e estrutura convencional de concreto armado em um edifício residencial unifamiliar - Senise, Diogo Donato Souza (2021)
This study deals with a comparison of costs between a single-family house designed in reinforced concrete and with the structural masonry, with a fictitious project created for the comparison of budgets for this work. The work aims to obtain information about the construction systems through in-depth bibliographical and documental research, detailing their advantages and disadvantages and its main characteristics. For the comparison of costs, two structural projects were developed and budgeted, with both systems, for analysis and comparison of the main costs of each one of them. From the analysis of the results obtained, it can be concluded that the use of structural masonry resulted in savings of R$ 10.452,69 in relation to reinforced concrete. Considering that only some stages of the work were budgeted, this percentage could be reduced in relation to the total cost, but in general, it allows us to conclude that structural masonry is an alternative to the conventional concrete structure in single-family houses.